Field Observations During the Sixth Microwave Water and Energy Balance Experiment (MicroWEX-6): from June 19 through November 30, 2006 - Fei Yan; Hwan Hee Han; Ruofan Yang; Joaquin Casanova; Jasmeet Judge; Jennifer Jacobs; Orlando Lanni; Larry Miller (EDIS)
Circular 1515, a 56-page illustrated report by Fei Yan, Hwan Hee Han, Ruofan Yang, Joaquin Casanova, Jasmeet Judge, Jennifer Jacobs, Orlando Lanni, and Larry Miller, presents the results of experiments using microwave remote sensing to determine root-zone soil moisture at UF/IFAS PSREU. Published by the UF Department of Agricultural and Biological Engineering, May 2007.